Soluble CD30, the Immune Response, and Acute Rejection in Human Kidney Transplantation: A Systematic Review and Meta-Analysis - Mirzakhani, Mohammad; Shahbazi, Mehdi; Akbari, Roghayeh; Dedinská, Ivana; Nemati, Eghlim; Mohammadnia-Afrouzi, Mousa (Frontiers in Immunology, 2020)
Soluble CD30 (sCD30) is considered as a marker for the activated immune system in which T cells can damage the allograft. Some studies reported that post-transplant sCD30 can predict early acute rejection and thereby can be used as a biomarker to detect acute rejection. However, several other studies found no relation between post-transplant sCD30 and acute rejection. This meta-analysis study aims to answer this main question of whether sCD30 can help clinicians to monitor transplant recipients. The electronic databases, including PubMed, Web of Science, ProQuest, Embase, Scopus, Google Scholar, the gray literature, and the key journals, were searched for observational studies from 1 January 1990 up to 30 April 2018. Eighteen studies, with a total of 1,453 patients, were included in this study. With regard to the different measurement times, post-transplant sCD30, which were separately analyzed, was divided into 5 groups, (i.e., 1-week, 2-week, 3-week, 4-week, and 1-month post-transplant sCD30). All groups indicated a strong association between sCD30 and the acute rejection. The standardized mean difference (SMD) is 1.22 in 1-week, 0.77 in 2-week, 1.11 in 3-week, 1.27 in 4-week, and 0.71 in 1-month groups. The association between sCD30 and acute rejection was consistent across all the subgroup analyses. We found that post-transplant sCD30 had a strong association with kidney acute rejection. We also found that the deceased donors had more association with the high amount of sCD30 than living donors in patients with acute rejection. Finally, we realized that donor type was an important factor leading to the heterogeneous results in primary studies.